Propagation of Pineapple by Shoot Tip Culture (University of Khartoum Journal of Agricultural Sciences, 2025)
This study was conducted with the objective of modifying thecomposition of MS medium for the clonal propagation of pineapple usingshoot tips of "Smooth Cayenne" cultivar. Modifications were made onvarious medium components. Results showed that both MS salts at thefull or half strength were optimal, and there was no significant differencebetween them. Sucrose concentrations of 3% and 6% were better thanother concentrations tested for growth and development of plantlets. Thecultures responded positively to the increase of adenine sulfate and 80mg/l was the optimal. As for the additions of NAA and BA, alone or incombinations, the best results were recorded with the combination ofNAA at 0.01 mg/l, and BA at 3.0 mg/l where the largest number of shootswas obtained. Better explants performance was achieved on liquidmedium with cotton support compared to solid medium.
Keywords: In vitro; Ananas comosus; clonal propagation; tissue culture